Identifying behavioral phenotypes for childhood obesity. (1st August 2018) - Kral, Tanja V.E.; Moore, Reneé H.; Chittams, Jesse; Jones, Elizabeth; O'Malley, Lauren; Fisher, Jennifer O.
Abstract: Existing programs which aim to prevent and treat childhood obesity often do not take into account individual variation and the underlying mechanisms that impact child eating behavior. Individual differences in children's appetitive traits have been shown to appear as early as during infancy and become more pronounced as children grow older and become more exposed to the obesogenic food environment. Differences in genetic predispositions interacting with factors in children's early environment account in part for individual differences in appetitive traits. It is very likely that obesogenic eating phenotypes manifest themselves before the onset of childhood obesity. If so, identifying these phenotypes early is expected to move primary prevention strategies in a new direction and holds great potential to significantly enhance our ability to prevent childhood obesity. The aim of this narrative review is to discuss the role of behavioral phenotyping as an innovative approach for the development of more personalized obesity prevention and treatment interventions that are tailored to children's individual predispositions. We describe several examples of appetitive traits which have been linked to overeating and excess weight gain in children and thus may represent modifiable risk factors for future interventions. The review concludes with a comprehensive synthesis of opportunities for future human ingestive behavior research on identifying behavioral phenotypes for childhood obesity.